Hemoglobin-Improved Protection in Cultured Cerebral Cortical Astroglial Cells: Inhibition of Oxidative Stress and Caspase Activation - Amri, Fatma; Ghouili, Ikram; Tonon, Marie-Christine; Amri, Mohamed; Masmoudi-Kouki, Olfa (Frontiers in Endocrinology, 2017)
Oxidative stress plays a major role in triggering astroglial cell death in diverse neuropathological conditions such as ischemia and neurodegenerative diseases. Numerous studies indicate that hemoglobin (Hb) is expressed in both resting and reactive glia cells, but nothing is known regarding a possible role of hemoglobin on astroglial cells survival. Thus, the purpose of the present study was to investigate the potential glioprotective effect of Hb on hydrogen peroxide (H2O2)-induced oxidative stress and apoptosis in cultured rat astrocytes. Our study demonstrates that administration of graded concentrations of Hb (10-12 to 10-6 M) to H2O2-treated astrocytes reduce cell death in a concentration-dependent manner. H2O2 treatment induces the accumulation of reactive oxygen species (ROS) and nitric oxide (NO), a drop of the mitochondrial membrane potential and a stimulation of caspases-3/7 activity. Exposure of H2O2-treated cells to Hb was accompanied by a marked attenuation of ROS and NO surproduction, reduction of mitochondrial membrane potential and activation of caspases-3/7 activity. The protective action of Hb was blocked by the protein kinase A inhibitor H89, the protein kinase C inhibitor chelerythrine and the mitogen-activated protein (MAP)-kinase kinase (MEK) inhibitor U0126. Taken together, these data demonstrate for the first time that Hb is a glioprotective factor that protects astrocytes from apoptosis induced by oxidative stress and suggest that Hb may confer neuroprotection in neurodegenerative diseases. The anti-apoptotic activity of Hb on astrocytes is mediated through the protein kinase A, protein kinase C and MAPK transduction pathways, and can be accounted for by inhibition of oxidative stress-induced mitochondrial dysfunctions and caspases activation.